Square design: From digital analysis to urban design - Pezzica, C. (2021)
This work proposes and tests, through the application to a Portuguese case study (Largo da Graça in Lisbon historic center), an original method of analysis specifically oriented to the study of public squares. Collecting contributions from the disciplines of urban morphology, social studies, environmental and site analysis, the presented methodology aims to synchronously and multi-dimensionally characterize and classify urban spaces at a multi-scale scale level, by coordinating multiple tools and advanced analysis techniques, in a process whose ultimate goal is to understand and improve the quality of public open spaces and to encourage its appropriation and enjoyment by the local community and the visitors.